The Relationship and Impact of Sumatra Thawalib Padang Panjang on the Development of Education in Kerinci in the 20th Century - Jalwis; Mirdad, Jamal; Admizal, Iril (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
This article aims to analyze the relationship and impact between Sumatra Thawalib Padang Panjang and Thawalib Islamiyah Al Rawaniyah in Kerinci. Sumatra Thawalib is one model of Islamic education reform that has provided many changes and influences on the existence and educational institutions in Minangkabau and Kerinci. Before the 19th century AD, Kerinci had received educational influence from Minangkabau. From the use of surau to the emergence of Thawalib in Kerinci, there are at least two things that were formulated, namely the impact of Sumatra Thawalib on Thawalib Islamiyah and the relationship between the two educational institutions. The research method used is the historical method, which takes four stages: heuristics (data collection), source criticism, synthesis and historiography (writing). The research results show that the presence of Thawalib Islamiyah Al Rawaniyah in Kerinci was influenced by the Sumatra Thawalib Padang Panjang in the form of institutions, learning methods and curriculum. Thawalib Islamiyah Al Rawaniyah is a duplication of Sumatra Thawalib with several modifications. Therefore, a synergistic relationship between the two agencies is built.